The Role Of E-Trust As Mediation Effect Of E-Service Quality On Online Purchase Intention At Consumer Smes Culinary Sector In Special Region Of Yogyakarta - Dewi Shanti Nugrahani; Widji Astuti; Harsono Harsono (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This study aims to examine the role of e-trust as mediation effect of e-service quality on online purchase intention at consumer smes culinary sector in Special Region of Yogyakarta. The respondents in this study were consumers at Special Region of Yogyakarta. The number of respondents in this study were 200 respondents. Sampling is done by purposive sampling technique. This study uses Structural Equation Modeling (SEM) with AMOS as an analytical tool. Based on the results of data testing conducted, it shows that: (1) E-service quality has a significant effect on e-trust at consumer SMEs culinary sector in Special Region of Yogyakarta. (2) E-trust has a significant effect on e-service quality at consumer SMEs culinary sector in Special Region of Yogyakarta. (3) E-service quality has a significant effect on online purchase intention at consumer SMEs culinary sector in Special Region of Yogyakarta. (4) E-trust as mediation effect of e-service quality on online purchase intention at consumer smes culinary sector in Special Region of Yogyakarta.